2008
DOI: 10.1111/j.1742-4658.2008.06648.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic response of Pseudomonas putida during redox biocatalysis in the presence of a second octanol phase

Abstract: A key limitation of whole-cell redox biocatalysis for the production of valuable, specifically functionalized products is substrate/product toxicity, which can potentially be overcome by using solvent-tolerant micro-organisms. To investigate the inter-relationship of solvent tolerance and energy-dependent biocatalysis, we established a model system for biocatalysis in the presence of toxic low logP(ow) solvents: recombinant solvent-tolerant Pseudomonas putida DOT-T1E catalyzing the stereospecific epoxidation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
146
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 139 publications
(155 citation statements)
references
References 82 publications
(115 reference statements)
9
146
0
Order By: Relevance
“…In contrast, manifold overexpression of nearly all enzymes of the glycolytic enzymes in yeast did not increase the glycolytic activity (44). Similar to the observation made with E. coli, Pseudomonas strains challenged with redox biocatalysis react to this metabolic burden by increasing the glycolytic rate but simultaneously decreasing the specific growth rate (10). As redox biocatalysis is intrinsically coupled to both increased ATP and redox cofactor demand, it is not clear which of these two loads triggers the increased metabolic activity.…”
mentioning
confidence: 52%
See 3 more Smart Citations
“…In contrast, manifold overexpression of nearly all enzymes of the glycolytic enzymes in yeast did not increase the glycolytic activity (44). Similar to the observation made with E. coli, Pseudomonas strains challenged with redox biocatalysis react to this metabolic burden by increasing the glycolytic rate but simultaneously decreasing the specific growth rate (10). As redox biocatalysis is intrinsically coupled to both increased ATP and redox cofactor demand, it is not clear which of these two loads triggers the increased metabolic activity.…”
mentioning
confidence: 52%
“…To separate cells and toxic compounds that are frequently also characterized by a low water solubility, the latter are solved and extracted, in a second organic phase (32,36). However, solvents with good extraction characteristics for the biocatalytic compounds can be similarly toxic to the cells (10). Microorganisms react to this toxification by different mechanisms, including changes in cell membrane composition, active removal of the toxic substrate by energy-driven efflux pumps, and alteration of the energy metabolism, which significantly increase the cellular energy expenditure.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Blank et al (2008) reported net glucose uptake rates of 10-15 mmol glucose g À1 CDW h À1 for exponentially growing Pseudomonas putida strains in batch cultures in the presence of solvents, while for Pseudomonas sp. VLB120DC grown in a chemostat a rate of about 3 mmol glucose g À1 CDW h À1 has been published (Park et al, 2007).…”
Section: Influence Of Oxygen Supply On Metabolic Activity Of the Biofmentioning
confidence: 99%